Characterization of Torquetenovirus in amniotic fluid at the time of in utero fetal surgery: correlation with early premature delivery and respiratory distress - Tozetto-Mendoza, Tania Regina; da- Costa, A. Charlys; Moron, Antonio F.; Leal, Élcio; Lima, Silvia Helena; Ferreira, Noely Evangelista; Honorato, Layla; Paião, Heuder Gustavo Oliveira; Freire, Wilton Santos; Mendes-Correa, Maria Cássia; Witkin, Steven S. (Frontiers in Medicine, 2023)
Torquetenovirus (TTV) is a commensal virus present in many healthy individuals. Although considered to be non-pathogenic, its presence and titer have been shown to be indicative of altered immune status in individuals with chronic infections or following allogeneic transplantations. We evaluated if TTV was present in amniotic fluid (AF) at the time of in utero surgery to correct a fetal neurological defect, and whether its detection was predictive of adverse post-surgical parameters. AF was collected from 27 women by needle aspiration prior to a uterine incision. TTV titer in the AF was measured by isolation of viral DNA followed by gene amplification and analysis. The TTV genomes were further characterized and sequenced by metagenomics.Pregnancy outcome parameters were subsequently obtained by chart review. Three of the AFs (11.1%) were positive for TTV at 3.36, 4.16, and 4.19 log10 copies/ml. Analysis of their genomes revealed DNA sequences similar to previously identified TTV isolates. Mean gestational age at delivery was > 2 weeks earlier (32.5 vs. 34.6 weeks) and the prevalence of respiratory distress was greater (100% vs. 20.8%) in the TTV-positive pregnancies. TTV detection in AF prior to intrauterine surgery may indicate elevated post-surgical risk for earlier delivery and newborn respiratory distress.